Integrating Character Education into Ethical Use of Google Translate at Vocational Schools - Rizki Pratama; Erwin Harikurniawan; Syaichul Muchyidin (International Journal of Multidisciplinary Research of Higher Education, 2026)
This research aims to explore the role of character education in fostering students' digital responsibility and ethical behavior regarding the use of machine translation tools for academic purposes. The main focus of this research is the internalization of character education values such as honesty, responsibility, and academic integrity in students’ digital practices, particularly in their use of google translate. The study conducted a qualitative method with a case study approach, enabling an in depth understanding of the phenomenon within real social and education contexts. Data were collected through in depth interviews and classroom observations. The result show that character education significantly influences how students utilize Google Translate. Students who receive consistent character education demonstrate higher ethical awareness in using google translate, including the ability to distinguish between constructive academic assistance and academic plagiarism. Conversely, insufficient character development leads to increased dependence on google translate without critical reflection. The implications of the study underscore the importance of integrating character education into digital based curricula to foster ethical literacy and academic responsibility in the technological era. Schools are therefore encouraged to develop learning strategies that integrate character education with digital competencies, enabling students to use google translate wisely, responsibly, and ethically.